Exergy analysis of combined cycle of gas turbine and solid oxide fuel cell in different compression ratios - Fatahian, Esmaeel; Tonekaboni, Navid; Fatahian, Hossein (International Journal of Scientific World, 2016)
Due to the growing trend of energy consumption in the world uses of methods and new energy production systems with high efficiency and low emissions have been prioritized. Today, with the development of different systems of energy production, different techniques such as the use of solar energy, wind energy, fuel cells, micro turbines and diesel generators in cogeneration have been considered, each of these methods has its own advantages and disadvantages. Having a reliable energy generation system, inexpensive and availability the use of fuel cells as a major candidate has been introduced. Fuel cells converting chemical energy to electrical energy that today are one as a new technology in energy production are considered. In this paper fuel cell compression ratios 4, 4.1 and 4.2 at an ambient temperature of 298 K have been simulated and ultimately optimum ratio 4.1 for modeling has been selected. All components of cycle, including the stack of fuel cell, combustion chamber, air compressors, recuperator and gas turbine was evaluated from the viewpoint of exergy and exergy destruction rate was calculated by EES software.